The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/app.44478
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ionic liquid on the polymer–filler coupling and mechanical properties of nano‐silica filled elastomer

Abstract: The natural rubber (NR) nanocomposites were fabricated by filling ionic liquid (1-allyl-3-methyl-imidazolium chloride, AMI) modified nano-silica (nSiO 2 ) in NR matrix through mechanical mixing and followed by a cure process. Based on the measurements of differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), solid state nuclear magnetic resonance spectroscopy, and Raman spectroscopy, it was proved that AMI could interact with nSiO 2 through hydrogen bonds. With the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Crosslinking density (v c ) of NBR in the nanocomposites was calculated according to Flory-Rehner equation [44][45][46]…”
Section: Crosslinking Densitymentioning
confidence: 99%
“…Crosslinking density (v c ) of NBR in the nanocomposites was calculated according to Flory-Rehner equation [44][45][46]…”
Section: Crosslinking Densitymentioning
confidence: 99%
“…Besides, the absorption peaks appearing at 2,928 and 2,857 cm1 in the spectra of silica‐A, silica‐T as well as silica‐TA correspond to the asymmetric and symmetric vibrations of methylene , indicating the TESPT is grafted on the silica surface of silica‐T and silica‐TA. When compared with pristine silica, the hydroxyl peak of silica‐A, silica‐T and silica‐TA downshift from 3,467 to 3,434 normalcnormalm1, indicating the hydrogen bond between AMI and silica as well as that between TESPT and silica , which were displayed in Fig. .…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, it has been reported that improved mechanical properties of SBR/silica composites can be achieved through using the ionic liquids, 1‐methylimidazolium mercaptopropionate or 1‐methylimidazolium methacrylate as coupling agent. Additionally, 1‐allyl‐3‐methyl‐imidazolium chloride (AMI) has been used to strengthen the interaction between silica and natural rubber . However, the interaction between silica and ionic liquid is usually weak non‐covalent interaction like hydrogen bonds, which results in restricted performance of rubber/silica composites.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the significant interfacial interactions between filler and rubber will lead to the formation of BRC . As a consequence, the BRC is usually used to measure the strength of interaction between filler and rubber chains …”
Section: Resultsmentioning
confidence: 99%
“…The weight of the samples before and after extraction was measured and the BRC was calculated according to the following equation: Bound rubber%=w2w1mf/()mf+mrw1mr/()mf+mr×1000.25em where w 2 is the weight of sample after drying and w 1 is the weight of the sample before swelling. m f and m r are the fraction of filler and rubber in the compound, respectively . The results were averaged over three samples.…”
Section: Methodsmentioning
confidence: 99%